2013
DOI: 10.1021/ja403255s
|View full text |Cite
|
Sign up to set email alerts
|

C2′-OH of Amphotericin B Plays an Important Role in Binding the Primary Sterol of Human Cells but Not Yeast Cells

Abstract: Amphotericin B (AmB) is a clinically vital anti-mycotic but is limited by its severe toxicity. Binding ergosterol, independent of channel formation, is the primary mechanism by which AmB kills yeast, and binding cholesterol may primarily account for toxicity to human cells. The leading structural model predicts that the C2′ hydroxyl group on the mycosamine appendage is critical for binding both sterols. To test this, the C2′ hydroxyl group was synthetically deleted and the sterol binding capacity of the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(82 citation statements)
references
References 60 publications
(69 reference statements)
2
76
0
2
Order By: Relevance
“…Recent efforts to improve the AmB therapeutic index have yielded a new derivative (C2=deOAmB), which binds ergosterol but not cholesterol (83). C2=deOAmB is toxic to yeasts but not to human primary kidney cells, confirming the role that cholesterol binding to AmB plays in developing drug nephrotoxicity.…”
Section: The Development Of Amb Toxicity and Resistance In Cholesteromentioning
confidence: 96%
“…Recent efforts to improve the AmB therapeutic index have yielded a new derivative (C2=deOAmB), which binds ergosterol but not cholesterol (83). C2=deOAmB is toxic to yeasts but not to human primary kidney cells, confirming the role that cholesterol binding to AmB plays in developing drug nephrotoxicity.…”
Section: The Development Of Amb Toxicity and Resistance In Cholesteromentioning
confidence: 96%
“…74 The prototype of these derivatives is amphotericin B with a C'2 hydroxyl group deletion, which allows it to only bind to fungal ergosterol and not mammalian cholesterol. 75 In vivo toxicity and therapeutic experiments using a systemic candidiasis murine model demonstrated that amphotericin B methyl urea (AmBMU) was less toxic and more effective than the traditional deoxycholate amphotericin B formulation. 74 These results contribute to the exciting progress in antifungal drug development linked to the gold standard antifungal agent amphotericin B.…”
Section: Polyenesmentioning
confidence: 99%
“…An analogue in which the mirror image of 3, 6 dideoxy 3-amino--D-glucose replaced mycosamine was also inactive (Croatt and Carreira, 2011). Burke and co-workers found that synthetic 2′-deoxy amphotericin B (lacking the 2′ hydroxyl on the mycosamine sugar) was active and had increased specificity for ergosterol-containing membranes (Wilcock et al, 2013). However, this analogue could not be chemically synthesised in large quantities (Davis et al, 2015).…”
Section: Glycosylationmentioning
confidence: 99%